Checklist For Autism Spectrum Disorder As An In-Class Observation Tool For Teachers - W. Król-Gierat (Zenodo, 2014)
The majority of Special Educational Needs checklists are intended for preliminary screening in the special education disability process. The aim of the present paper is to present their potential usefulness as in-class observation tools for teachers working with students who have already been diagnosed with a disorder. A checklist may complement and organize information about a given child, which is indispensable to improve his or her condition. The case of a Polish boy with autism will serve as an example. Last but not least, alternative uses of checklists are suggested in the article. : {"references": ["G. Akhgarnia, \"Overconnectivity in brain found in autism,\" in SDSUNewsCentre,2011: http://newscenter.sdsu.edu/sdsu_newscenter/news.aspx?s=73005 [accessed 29.12.2013]", "American Psychiatric Association, Diagnostic and statistical manual of mental disorders (4th ed.). Washington, DC, 1994.", "S. Baron-Cohen, Autism and Asperger Syndrome. Oxford: Oxford University Press, 2008.", "G. Hannell, Identifying children with special needs. Checklists and action plans for teachers. Thousand Oaks, CA: Corwin Press, 2006, pp. 1-28.", "M. A. Just, T. A. Keller, V. L. Malave, R. K. Kana, S. Varma, \"Autism as neural systems disorder: A theory of frontal-posterior underconnectivity,\", in Neuroscience and Behavioral Reviews 35, 2012, pp. 1292-1313.", "J. Kormos, A. M. Smith, Teaching languages to students with Specific Learning Differences. Bristol, Buffalo, Toronto: Multilingual Matters, 2012, pp. 52-53.", "Matuzaki H., Iwata K., T. Manabe, N. Mori, \"Triggers for autism: genetic and environmental factors,\" in Journal of Central Nervous System Disease 4, 2012, pp. 27-36.", "B. Quinn, A. Malone, Autism, Asperger Syndrome and Pervasive Developmental Disorders. London and Philadelphia: JKP, 2011.", "D. A. Sousa, How the special needs brain learns. Thousand Oaks, CA: Corwin Press, 2007, pp. 179-195.\n[10]\tS. Steffenburg, C. Gillberg, L. Hellgren, L. Andersson, I. C. Gillberg, G. Jakobsson, M. Bohman, \"A twin study of autism in Denmark, Finland, Iceland, Norway and Sweden,\" in Journal of Child Psychology and Psychiatry30(3), 1989, pp. 405\u2013416.\n[11]\tP. Williams (ed.), A glossary of Special Education. Philadelphia: Open University Press, 1988, p. 20."]}